2018
DOI: 10.1111/tesg.12344
|View full text |Cite
|
Sign up to set email alerts
|

Counter–Urbanisation as the Growth of Small Towns: Is the Capital Region of India Prepared?

Abstract: India's increased pace of urbanisation is evident, but the question remains as to whether India can harness its developmental potential by providing social infrastructure to meet its projected growth. This paper investigates the urbanisation trajectory with respect to the provision of social infrastructure in the Capital Region of India. First, it applies the differential urbanisation model and predicts counter-urbanisation to be the next stage of development. Second, using socioeconomic indicators, the paper … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Owen and Jacqueline [21] found that the counter urbanization in Zambia has mainly been affected by population migration. Jain and Korzhenevych [22] predicted India's counter urbanization process and put forward corresponding policy recommendations. Other scholars have explored the relationship between the spatial distribution of the population and socioeconomic phenomena.…”
Section: Spatial Distribution Of the Populationmentioning
confidence: 99%
“…Owen and Jacqueline [21] found that the counter urbanization in Zambia has mainly been affected by population migration. Jain and Korzhenevych [22] predicted India's counter urbanization process and put forward corresponding policy recommendations. Other scholars have explored the relationship between the spatial distribution of the population and socioeconomic phenomena.…”
Section: Spatial Distribution Of the Populationmentioning
confidence: 99%